Local Research and Glocal Perspectives in English Language Teaching Teaching in Changing Times - Khan, Rubina; Bashir, Ahmed; Basu, Bijoy Lal.; Uddin, Md. Elias (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides an overview of current trends and developments in the field of English language education in changing times. It features contributions by academics from different parts of the world and brings together local and global perspectives on a range of issues in curriculum, materials, ELT practices, educational technology, assessment, and teacher education. It shares the experiences and practices of young and experienced professionals in diverse contexts.
Introduction -- Part 1: Socio-cultural perspectives in ELT -- ELT and development in Bangladesh: A critical overview -- Students' uptake of translanguaging pedagogies and translanguaging-oriented assessment in an ELT classroom at a Bangladeshi university -- Culture in language teacher education: A South Asian perspective -- Snowflakes versus ice cubes in creative language use -- Part 2: Curriculum and materials -- Economisation of the secondary English curriculum in Bangladesh -- Outcome-based living ELT curriculum in higher education in Bangladesh -- Enacted curriculum of private English kindergartens in Korea: Cases of three play-based English kindergartens in Seoul -- "Stories About Ourselves": Collaboration, teacher development, and creating culturally relevant graded EFL reading materials for Bangladeshi learners -- The challenges of developing ELT materials for higher secondary schools in Bangladesh: The case of the English textbook -- Rhizomatic literacy through graphic novels -- Part 3: Educational technology -- Students' evolved beliefs of TELL constraints and benefits: Learner voices from an EAP programme -- Teacher initiatives for technology integration in higher education in Bangladesh -- Wiki-based collaborative writing: Undergraduate learners' perspectives -- Using digital tools to enhance student engagement in online learning: An action research study -- Part 4: ELT practices -- Re-envisioning English language teaching in a post-COVID world: Using language education for sustainable development -- Exploring language learning attitudes through diaries -- Second language writing instruction in Iran: The status quo and future research agenda -- Impact of textual enhancement on EFL learners' noticing and acquisition of noun and verb phrases -- Disruptive perspectives and reinvention: Why and how for the English learners -- Part 5: Assessment -- Practical applications of learning-oriented assessment (LOA) -- Exploring assessment literacy of tertiary-level teachers in Bangladesh -- Impact of a national English as a foreign language test on parents in Nepal -- Common item violations in multiple choice questions in Bangladeshi recruitment tests -- Part 6: Teacher education -- Researching and developing teacher expertise in the Global South: Local and transferrable solutions -- The professional, pedagogical, and personal impacts of being a volunteer teacher trainer: Case studies from teachers helping teachers -- English language teacher education and policy changes in multilingual Indonesia -- "Not Proper Teaching": The beliefs and experiences of novice native English language teachers in the UK -- (Re)thinking initial teacher education curriculum: Towards equitable, crisis-ready TESOL -- Closing thoughts.
Keywords: Language and languages-Study and teaching; Teachers-Training of; Educational sociology; Education and state; Language Education; Teaching and Teacher Education; Sociology of Education; Educational Policy and Politics